3D sand mould printing: a review and a new approach. Issue 2 (12th March 2018) - Zhao, Donghua; Guo, Weizhong; Zhang, Baibing; Gao, Feng
Abstract : Purpose: The purpose of this paper is to review available technologies, analyse their features, propose a new approach of 3D sand mould printing based on line forming, introduce the manufacturing principle and show advantages of this approach, especially for larger parts with large Z steps in the build, such as 2 mm stepwise. Design/methodology/approach: This paper introduces 3D sand mould printing, compares and analyses technological process and existing fabrication approaches among available technologies first. Then, a new approach of 3D sand mould printing is proposed to improve build speed. In addition, the proposed system will be analysed or benchmarked against existing systems. Findings: A new approach based on line forming of sand mould printing is put forward by reviewing and analysing available technologies, to improve build speed from the aspect of basic moulding movement instead of optimization of moulding methods and process parameters. The theoretical calculation and analysis shows that build speed can be improved greatly, and it is more suitable for the manufacture of large-scale casting's sand mould when considering dimensional accuracy and printing error, as well as uniformity of each layer. Research limitations/implications: The specific implement scheme of line forming and nozzle's specific structure of this new approach need further study. Practical implications: Much higher build speed of 3D sand mould printing with new approach brings evident implication for moulds companies and manufacturing industry, having a far-reaching influence on the development of national economy. Originality/value: This paper reviews available technologies and presents a new approach of 3D sand mould printing for the first time. Analysis of the new approach shows that this new method of sand mould printing can boost build speed greatly. So, its application prospect is great.